War Finance and Logistics in Late Imperial China : a Study of the Second Jinchuan Campaign (1771-1776). - Theobald, Ulrich (Monies, markets, and finance in East Asia, 1600-1900., 2013)
In his book War Finance and Logistics in Late Imperial China, Ulrich Theobald analyzes how the Qing dynasty (1644 - 1911) laid the organizational base for the spectacular expansion of its territory.